Toll Like Receptor 4 Mediated Lymphocyte Imbalance Induces Nec-Induced Lung Injury. Issue 2 (August 2019) - Jia, Hongpeng; Sodhi, Chhinder P.; Yamaguchi, Yukihiro; Lu, Peng; Ladd, Mitchell R.; Werts, Adam; Fulton, William B.; Wang, Sanxia; Prindle, Thomas; Hackam, David J.
Abstract : ABSTRACT: Necrotizing enterocolitis (NEC) is the leading cause of death from gastrointestinal disease in premature infants, and is associated with the development of severe lung inflammation. The pathogenesis of NEC-induced lung injury remains unknown, yet infiltrating immune cells may play a role. In support of this possibility, we now show that NEC in mice and humans was associated with the development of profound lung injury that was characterized by an influx of Th17 cells and a reduction in T regulatory lymphocytes (Tregs). Importantly, the adoptive transfer of CD4 + T cells isolated from lungs of mice with NEC into the lungs of immune incompetent mice (Rag1 −/− mice) induced profound inflammation in the lung, while the depletion of Tregs exacerbated NEC induced lung injury, demonstrating that imbalance of Th17/Treg in the lung is required for the induction of injury. In seeking to define the mechanisms involved, the selective deletion of t oll-l ike r eceptor 4 (TLR4) from the Sftpc1 pulmonary epithelial cells reversed lung injury, while TLR4 activation induced the Th17 recruiting chemokine (C-C motif) ligand 25 (CCL25) in the lungs of mice with NEC. Strikingly, the aerosolized inhibition of both CCL25 and TLR4 and the administration of all trans retinoic acid restored Tregs attenuated NEC-induced lung injury. In summary, we show that TLR4 activation in S urfactant p rotein C -1 (Sftpc1) cells disrupts the Treg/Th17 balance in the lung via CCL25 leading to lung injury after NEC and reveal that inhibition of TLR4 and stabilization of Th17/Treg balance in the neonatal lung may prevent this devastating complication of NEC. Abstract : Supplemental Digital Content is available in the text